A Cytohistological Correlation Study of Thyroid Lesions: Our Institutional Experience - BK Pokhrel, Sailendra (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Thyroid neck masses are common clinical presentations, encompassing a spectrum of benign and malignant conditions. Fine-needle aspiration cytology (FNAC) serves as an initial diagnostic tool for evaluating these masses, while histopathological examination (HPE) remains the gold standard for definitive diagnosis. Method: This prospective study reviewed data from 49 patients with thyroid swelling who underwent FNAC followed by surgical resection at our institution. FNAC results were categorized into colloid goitre, papillary thyroid carcinoma, follicular neoplasm, thyroiditis, Hurthle cell adenoma and inconclusive . HPE findings were used to determine sensitivity, specificity, and overall diagnostic concordance. Result: FNAC demonstrated a high concordance rate (92%) with HPE. Colloid goitre was accurately diagnosed in 97% (33/34) of cases, and thyroiditis in 100% (2/2) of cases. For papillary thyroid carcinoma, FNAC identified 5 cases, with HPE detecting an additional case. Challenges were noted in diagnosing follicular neoplasms, where HPE revealed 3 adenomas and 2 carcinomas. Sensitivity exceeded 90% for colloid goitre and thyroiditis, though specificity was lower for follicular neoplasms due to cytological limitations. Conclusion: FNAC is an effective and reliable preliminary diagnostic tool for thyroid neck masses; however, it has limitations in differentiating follicular neoplasms and some malignancies. HPE remains indispensable for definitive diagnosis. Combining both methods ensures accuracy and facilitates appropriate management.